2007
DOI: 10.1096/fj.07-8173com
|View full text |Cite
|
Sign up to set email alerts
|

Retinol‐binding protein‐4 attenuates insulin‐induced phosphorylation of IRS1 and ERK1/2 in primary human adipocytes

Abstract: Reduced sensitivity to insulin in adipose, muscle, and liver tissues is a hallmark of type 2 diabetes. Animal models and patients with type 2 diabetes exhibit elevated levels of circulating retinol-binding protein (RBP4), and RBP4 can induce insulin resistance in mice. However, little is known about how RBP4 affects insulin signaling. We examined the mechanisms of action of RBP4 in primary human adipocytes. RBP4-treated adipocytes exhibited the same molecular defects in insulin signaling, via IRS1 to MAP kinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(38 citation statements)
references
References 25 publications
3
35
0
Order By: Relevance
“…In contrast, the molecular mechanisms behind insulin resistance in humans are poorly understood (2,3). In T2D, insulininduced phosphorylation of IRS1 on tyrosine residues has been shown to be impaired in both human skeletal muscle (4)(5)(6)(7) and adipose tissue (8,9). In adipocytes from patients with T2D we have found that a positive feedback control loop, involving phosphorylation of IRS1 at serine-307 (human sequence, corresponding to serine-302 in the murine sequence) is not fully functional (10,11).…”
Section: Introductionmentioning
confidence: 82%
“…In contrast, the molecular mechanisms behind insulin resistance in humans are poorly understood (2,3). In T2D, insulininduced phosphorylation of IRS1 on tyrosine residues has been shown to be impaired in both human skeletal muscle (4)(5)(6)(7) and adipose tissue (8,9). In adipocytes from patients with T2D we have found that a positive feedback control loop, involving phosphorylation of IRS1 at serine-307 (human sequence, corresponding to serine-302 in the murine sequence) is not fully functional (10,11).…”
Section: Introductionmentioning
confidence: 82%
“…While studying altered insulin signaling in adipocytes treated with RBP4, it was proposed that RBP4 inhibits phosphorylation at the site of the insulin receptor substrate 1 that may be responsible for integrating nutrient sensing with insulin signaling (91). In a study focusing on the role of inflammation in RBP4 expression in human adipocytes, RBP4 was unexpectedly downregulated by tumor necrosis factor a (TNFa) (92).…”
Section: Studies On Human Adipocytesmentioning
confidence: 99%
“…All these findings together provide an evidence for negative relationship between RBP4 expression and secretion from bovine adipocytes and the adipogenesis. This notion can be supported by the ideas stated that insulin resistance in mice is related to adipose-derived rather than liver-derived RBP4 because manipulation of adipose-derived RBP4 enhanced insulin sensitivity without affecting serum RBP4 level (Yang et al, 2005) Ost et al (2007 added, all trans RA treatment down-regulated RBP4 expression in mice adipocytes not in liver while it enhanced glucose tolerance and insulin sensitivity of the animals. Although all of these evidence indicating a negative correlation between RBP4 expression and secretion from bovine adipocytes and adipogenesis, we found that RA decreased both adipogenesis and RBP4 expression and secretion in intramuscular adipocytes cultured in normal glucose medium.…”
Section: Discussionmentioning
confidence: 87%
“…These differences in RBP4 secretion from bovine adipocytes may have impact on the role of RBP4 in adipogenesis in bovine adipocytes. Because it was indicated that RBP4, especially that produced from adipose tissue, interferes with glucose uptake and insulin sensitivity in mice adipocytes (Yang et al, 2005) and attenuates insulin signaling in human adipocytes (Ost et al, 2007). Smith et al (2009) and our previous study (data under review) reported that glucose is essential for adipogenesis in bovine intramuscular adipocytes.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation